2022
DOI: 10.1002/jmv.28123
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome sequencing of SARS‐CoV‐2: Comparison of target capture and amplicon single molecule real‐time sequencing protocols

Abstract: Fast, accurate sequencing methods are needed to identify new variants and genetic mutations of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) genome. Single‐molecule real‐time (SMRT) Pacific Biosciences (PacBio) provides long, highly accurate sequences by circular consensus reads. This study compares the performance of a target capture SMRT PacBio protocol for whole‐genome sequencing (WGS) of SARS‐CoV‐2 to that of an amplicon PacBio SMRT sequencing protocol. The median genome coverage was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The proportion of sample sequence failures obtained with the target capture method in this study of Omicron variants was similar to that obtained for the Alpha/Delta variants 27 and the complete genome coverages of the Omicron (median >98%) and Alpha/Delta variants (median >99%) were also similar 27 . However, the proportion of samples with a complete genome coverage of >95% was slightly lower (55%) than for the Alpha/Delta variants (63%), perhaps because the Omicron samples of this study had lower viral loads.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The proportion of sample sequence failures obtained with the target capture method in this study of Omicron variants was similar to that obtained for the Alpha/Delta variants 27 and the complete genome coverages of the Omicron (median >98%) and Alpha/Delta variants (median >99%) were also similar 27 . However, the proportion of samples with a complete genome coverage of >95% was slightly lower (55%) than for the Alpha/Delta variants (63%), perhaps because the Omicron samples of this study had lower viral loads.…”
Section: Discussionsupporting
confidence: 78%
“…We used the PacBio HiFiViral for SARS‐CoV‐2 workflow, High‐Throughput Multiplexing 1.2 kb Amplicons for Full‐Viral Genome Sequencing of SARS‐CoV‐2, based on 29 1.2 kb amplicons across the SARS‐CoV‐2 genome (hereafter referred to as amplicon) with improved primers for amplicons A1, A5, A10, A15, A21, A24, and A28, which have mutation‐induced reduced coverage in Omicron variants (Table 1). The protocol was done as previously described 27 . Briefly, we first generated cDNAs and then obtained the 29 amplicons by two multiplex PCRs (with two primers pools, Pool 1 and Pool 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expectedly, they found that taxon-specific panels produced the best results compared to broader-range panels (e.g., respiratory viruses panel). Beyond the choice of panels, studies also investigated and verified the efficacy of HC for SARS-CoV-2 sequences across bioinformatic pipelines [ 241 ], sequencing platforms [ 242 , 243 ], and even library preparation methods [ 244 ]. Generally, molecular techniques (e.g., metagenomic sequencing, HC, and PCR) performed comparably, but in SARS-CoV-2, as the pathogen has a relatively small genome (~30 kb), enrichment of sequences can be executed using dedicated primers for the entire genome (e.g., ARCTIC 4.1).…”
Section: Case Study: Sars-cov-2mentioning
confidence: 99%